Revealing the Antioxidant Content in Banana Plants: A Nutritional Perspective and Health Benefits - Ummum, Andi; Fawwaz, Muammar; Yuliana, Dewi (Universitas Muslim Indonesia, 2025)
The banana (Musa paradisiaca L.) is a fruit widely consumed across tropical regions and recognized for its rich nutritional value and diverse bioactive compounds that contribute to human health. This study aims to evaluate the antioxidant content of banana plants from both nutritional and pharmacological perspectives through a comprehensive literature review. The review was conducted using scientific articles and official guidelines published between 2015 and 2025. The findings indicate that the banana pulp contains essential nutrients such as carbohydrates (27%), proteins (1%), and a variety of vitamins and minerals including calcium, potassium, and iron. In contrast, the banana peel, often considered agricultural waste, is abundant in bioactive phytochemicals such as flavonoids, polyphenols, tannins, saponins, and terpenoids, which contribute to its antioxidant potential. Antioxidant activity in banana extracts has been reported using various analytical methods, including DPPH (IC₅₀ = 439.12 µg/mL), FRAP (26.5828 mg QE/g extract), ABTS (IC₅₀ = 60.50–95.85 ppm), CUPRAC (EC₅₀ = 101–150 µg/mL), and CAA (397 ± 5 µmol TE/100 g) assays. Moreover, fruit maturity influences antioxidant capacity, with unripe banana peels generally exhibiting higher antioxidant activity than ripe ones. These results highlight that banana plants, particularly their peels, possess considerable potential as natural antioxidant sources for use in food, nutraceutical, and pharmaceutical applications. Furthermore, the valorization of banana peel aligns with the circular economy concept, promoting sustainable agricultural waste management and environmental conservation.